Alterations in the Staphylococcus epidermidis biofilm transcriptome following interaction with whole human blood. Issue 3 (10th February 2014) - França, Angela; Carvalhais, Virgínia; Maira‐Litrán, Tomás; Vilanova, Manuel; Cerca, Nuno; Pier, Gerald
Abstract Staphylococcus epidermidis biofilm formation on the surface of intravenous catheters is responsible for 22% of the cases of bloodstream infections, in patients in intensive care units in the USA. The ability of S. epidermidis to withstand the high bactericidal activity of human blood is therefore crucial for systemic dissemination. To identify the genes involved in the bacterium's survival, the transcriptome of S. epidermidis biofilms, upon contact with human blood, was assessed using an ex vivo model. Our results showed an increased transcription of genes involved in biosynthesis and metabolism of amino acids, small molecules, carboxylic and organic acids, and cellular ketones. One of the striking changes observed 4 h of S. epidermidis exposure to human blood was an increased expression of genes involved in iron utilization. This finding suggests that iron acquisition is an important event for S. epidermidis survival in human blood.